TEORI TRAIT AND FACTOR: MENELUSURI KETERBATASAN DAN ALTERNATIF PENDEKATAN KARIR DALAM PERSPEKTIF ISLAM - Irmayanti, I; Nurjannah, N (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
Counseling theories widely applied often tend to refer to Western approaches, even though as Muslims, it is crucial for us to develop these approaches by incorporating Islamic dimensions. Enriching the counseling theories adopted from the West, emphasizing Islamic values and principles can provide a more comprehensive and contextual nuance in the counseling process. Thus, we can establish a more holistic counseling foundation aligned with Islamic spiritual and cultural values, making it more effective in assisting individuals in achieving their mental and emotional well-being. This research aims to explain the limitations of the trait and factor theory in the context of career counseling and provide alternative counseling approaches to enhance it. The research employs a literature review method. The findings offer an analysis of the strengths and weaknesses of the trait and factor theory, along with several alternative counseling approaches suggested by the author to improve it.